THE INFLUENCE OF ICE BREAKER TO STUDENTS’ MOTIVATION IN TEACHING ENGLISH - Asti Solihat; Ayu Rindu Astuti; Intan Satriani (IKIP Siliwangi, 2020)
This research is aimed at exploring ice breaker technique in teaching English for student at Junior High School in Cimahi. Based on the important of teaching English in Indonesia as foreign language. So by doing ice breaking before learning, it is expected that students can focus on the learning English process. In this research the writer used case study and qualitative research method. The subject of this research was on of an English teacher at One of Junior High School in Cimahi. The instrument of this research are observation, and interview. The result of this research is students’ to be focus and fun on learning English in the class.